6th World Congress of Biomechanics (WCB 2010). August 1-6, 2010 Singapore In Conjunction with 14th International Conference on Biomedical Engineering (ICBME) and 5th Asia Pacific Conference on Biomechanics (APBiomech) - Lim, C. T.; Goh, J. C. H.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
Biomechanics covers a wide field such as organ mechanics, tissue mechanics, cell mechanics to molecular mechanics. At the 6th World Congress of Biomechanics WCB 2010 in Singapore, authors presented the largest experimental studies, technologies and equipment. Special emphasis was placed on state-of-the-art technology and medical applications. This volume presents the Proceedings of the 6th WCB 2010 which was hold in conjunction with 14th International Conference on Biomedical Engineering (ICBME) & 5th Asia Pacific Conference on Biomechanics (APBiomech). The peer reviewed scientific papers are arranged in the six themes Organ Mechanics, Tissue Mechanics, Cell Mechanics, Molecular Mechanics, Materials, Tools, Devices & Techniques, Special Topics.
Theme 1: Special Topics -- Theme 2: Organ Mechanics -- Theme 3: Tissue Mechanics -- Theme 4: Cell Mechanics -- Theme 5: Molecular Mechanics -- Theme 6: Materials, Tools, Devices and Techniques -- The 13th International Symposium of NanoBME -- Young Investigator Award Papers.
Keywords: Engineering; Cell biology; Biophysics; Biological physics; Continuum mechanics; Biomedical engineering; Biomaterials; Engineering; Biomedical Engineering; Cell Biology; Biophysics and Biological Physics; Biomaterials; Continuum Mechanics and Mechanics of Materials; Electronic books